Constrained spectral clustering via multi-layer graph embeddings on a Grassmann manifold - Trokicić, Aleksandar; Todorović, Branimir (Zielona Góra: Uniwersytet Zielonogórski)
We present two algorithms in which constrained spectral clustering is implemented as unconstrained spectral clustering on a multi-layer graph where constraints are represented as graph layers. By using the Nyström approximation in one of the algorithms, we obtain time and memory complexities which are linear in the number of data points regardless of the number of constraints.
Keywords: spectral clustering; constrained clustering; multi-layer graph; Grassmann manifold; Nyström method; Laplacian matrix